2008
DOI: 10.1016/j.pbb.2008.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal regulation of contextual cue-induced reinstatement of cocaine-seeking behavior

Abstract: Associations between cocaine and cues facilitate development and maintenance of addiction. We hypothesized that the ventral hippocampus is important for acquisition of these associations. Rats were trained to self-administer cocaine, with or without pre-exposure to distinct sets of cocaine- and saline-paired contextual cues. Next, rats were conditioned for 3 days with the distinct sets of contextual cues paired with cocaine and saline along with distinct discrete cues. Vehicle or lidocaine was infused into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…These findings expand upon our previous study (Lasseter et al, 2011), in which BM-induced functional disconnection of the OFC and BLA inhibited drug context-induced reinstatement of cocaine-seeking behavior without altering food-reinforced instrumental responding or general motor activity. These findings also add to a larger literature that indicates that the OFC and BLA are critical for explicit cue-and drug context-induced cocaine-seeking behaviors (Atkins et al, 2008;Crombag et al, 2008;Fuchs et al, 2005Fuchs et al, , 2004Fuchs et al, , 2008Grimm and See, 2000;Hamlin et al, 2008;Kantak et al, 2002;Lasseter et al, 2009Lasseter et al, , 2011McLaughlin and See, 2003;Neisewander et al, 2000;See et al, 2001;Zavala et al, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…These findings expand upon our previous study (Lasseter et al, 2011), in which BM-induced functional disconnection of the OFC and BLA inhibited drug context-induced reinstatement of cocaine-seeking behavior without altering food-reinforced instrumental responding or general motor activity. These findings also add to a larger literature that indicates that the OFC and BLA are critical for explicit cue-and drug context-induced cocaine-seeking behaviors (Atkins et al, 2008;Crombag et al, 2008;Fuchs et al, 2005Fuchs et al, , 2004Fuchs et al, , 2008Grimm and See, 2000;Hamlin et al, 2008;Kantak et al, 2002;Lasseter et al, 2009Lasseter et al, , 2011McLaughlin and See, 2003;Neisewander et al, 2000;See et al, 2001;Zavala et al, 2008).…”
Section: Discussionsupporting
confidence: 62%
“…Blocking this neurogenesis in rodents leads to increased cocaine self-administration (Noonan, Bulin, Fuller, & Eisch, 2010). Extensive preclinical work has shown that the hippocampus, along with the amygdala, are involved in stress and cocaine cue induced reinstatement (Atkins, Mashhoon, & Kantak, 2008; Belujon & Grace, 2011; Fuchs, Eaddy, Su, & Bell, 2007; Fuchs et al, 2005; Rogers & See, 2007; See, 2005). Unlike the prefrontal cortex, the hippocampus is not typically smaller in cocaine users than controls (Makris et al, 2004; Mei et al, 2015; Xu et al, 2014), and one group has found that hippocampal volume in individuals entering treatment was prospectively associated with more drug use as measured by urine drug screens and self-report (Xu et al, 2014).…”
Section: Section 2: Executive and Limbic System Irregularities In Cocmentioning
confidence: 99%
“…An automatic reflex conditioner 7531 (inside dimensions 390×95×165 mm, Cat No: 7530, Ugo Basile, Italy) was used and the protocol was adapted from published papers (Atkins et al, 2008;Saxe et al, 2006). Freezing was defined as absence of movement except for respiration.…”
Section: Trace Fear Conditioning Testmentioning
confidence: 99%